Nucellar beak structure and pollen tube growth in Cucurbitaceae - Lizarazu, Mabel Angela (2014)
The nucellar beak is a proboscis-like outgrowth of the nucellus at the micropylar end, being the obliged path for the pollen tube entering the ovule. Among the few angiosperm families with nucellar beak, Cucurbitaceae is remarkable because the pollen tube may develop at least two types of growth within the nucelar beak: tubular, and ampulliform. Wondering about the possibility that Cucurbitaceae ovules may express some histological variation that could be related to pollen tube growth within the nucellar beak, we performed a compared anatomical, histochemical study of the nucellar beak and pollen tube growth of ten species of Cucurbitaceae. Results show that Cucurbitaceae ovules are diverse in size and proportions (of integuments, nucellar body, and nucellar beak), and they have at least four types of nucellar beak histology: pectic-tracked, secretory-like, amylaceous, and mixed. Amylaceous and mixed nucellar beaks are related to the ampulliform growth of the pollen tube, which could have appeared independently in most derived tribes of Cucurbitaceae, although information about nucellar beak structure in the basal tribes is still needed. In addition, the understanding of the relation between amylaceous nucellar beaks and the ampulliform growth of the pollen tube, whose function is still to be discovered, might open the possibility of a unique model of pollen tube - ovule co-evolution in angiosperms.